Strategies for Mangrove Resource Management: Development of Natural Science Booklet Based on Mangrove Diversity in Gili Sulat, East Lombok - Diniyatushoaliha, Ainun; Mahmudah , Huraiza (International Journal of Science Education and Science, 2024)
The educational approach is one of the strategies in managing mangrove resources, especially mangroves in Gili Sulat. This study aims to develop a science booklet based on mangrove diversity in Gili Sulat, East Lombok. The method of collecting mangrove diversity data is a line transect. The type of research used is Research and Development with a 4-D model, namely defining, designing, developing, and disseminating. The results of the study are in the form of a science booklet design on mangrove diversity in Gili Sulat which has distinctive characteristics, describes the potential and benefits of mangrove forests, displays factual information on mangrove diversity in Gili Sulat, East Lombok, uses short, clear language, is easy to understand and comprehend, and uses an attractive visual display of images.